Investigation the position of wood and paper industry in the economic sector in Iran by input-output approach - maryam lashkarizadeh (Regional Information Center for Science and Technology (RICeST), 2016)
Considering the importance of the wood and paper industry for the Iranian economy and interaction and linkages between the wood and paper sector with other economic sectors. In order to do so, Input-Output table for 1380 and hypothetical extraction method has been used. Calculation of sensitivity index of publication as well as the wood and paper industry publishing strength index respectively with figures 451.2 and 378.1 suggests that this industry ranked first and third release power sensitivity in between sections is And this means that the wood and paper industry, more than the average total other sections with the other categories in this connection and communication as well as alike and more balanced sections. In the case of the hypothetical extraction method from the perspective of the production output decreased the amount of million 112345678 (Leontief pattern) and 132456789 cents (gosh pattern). In terms of stretching the production ranking 19 of 34 of its assigned section.